Gene expression profile in the activation of subperitoneal fibroblasts reflects prognosis of patients with colon cancer. Issue 6 (1st October 2015) - Yokota, Mitsuru; Kojima, Motohiro; Higuchi, Youichi; Nishizawa, Yuji; Kobayashi, Akihiro; Ito, Masaaki; Saito, Norio; Ochiai, Atsushi
Abstract : Tumors can create a heterogenetic tumor microenvironment. We recently identified the pathologically unique cancer microenvironment formed by peritoneal invasion (CMPI), and revealed that subperitoneal fibroblasts (SPFs) within peritoneal tissue play a crucial role in tumor progression through their interaction with cancer cells. Therefore, the genes in SPFs altered by cancer stimulation may include some biologically important factors associated with patient prognosis. In this study, we aimed to identify new biomarkers using genes specifically upregulated in SPFs by cancer‐cell‐conditioned medium (CCCM) stimulation (SPFs CCCM response genes; SCR genes) in colon cancer (CC). We constructed two frameworks using SCR gene data: a publicly released microarray dataset, and validation cases with freshly frozen CC samples to identify genes related to short recurrence‐free survival (RFS). In the first framework, we selected differentially expressed genes between the high and low SCR gene expression groups. In the second framework, genes significantly related to short RFS were selected by univariate analysis using all SCR genes, and multivariate analysis was performed to select robust genes associated with short RFS. We identified CTGF, CALD1, INHBA and TAGLN in the first framework, and PDLIM5, MAGI1, SPTBN1 and TAGLN in the second framework. Among these seven genes, high expression of three genes ( CALD1, TAGLN and SPTBN1 ) showed a poor prognosis in our validation cases. In a public microarray dataset, SCR gene expression was associated with the expression of ECM component, EMT, and M2‐macrophage associated genes, which was concordant with the pathological features of CMPI. Thus, we successfully identified new prognostic factors. Abstract : What's new? Peritoneal involvement is an important prognostic factor in colon cancer. Of particular consequence are tumor‐promoting interactions between subperitoneal fibroblasts (SPFs) and cancer cells in the peritoneal cancer microenvironment. In the present analysis of gene expression in cancer cell‐stimulated SPFs, elevated expression of three genes ( CALD1, TAGLN, and SPTBN1 ) was found to be associated with poor prognosis. The genes' altered expression was linked to changes in the expression of factors that contribute to the modification of the peritoneal cancer microenvironment. The three‐gene signature, discovered from global gene expression data in vitro, may be a clinically useful prognostic marker.